Percep????es sobre o uso das TICs por jovens da pedagogia e seus professores - Goulart, Ione Ferrarini (2016)
This work investigated the perception around the use of ICTs by pedagogy students and their professors with the ambition of (a) verify what is the young university students??? perception surrounding the use of the ICTs in their professors??? pedagogic practices; (b) check how the professors perceive their pedagogic practices in relation to the use of ICTs; and (c) analyse the common and divergent points of both perceptions. We opted for choosing a qualitative research and exploratory character generation with the utilization of the following data collection technics: focal group, questionnaire and interview. The study was fulfilled, at first, based on two focal groups??? data, made by researches of the research group Juventude, Educa????o e Tecnologias: Sociabilidades e Aprendizagens (Jetsa) ??? Youth, Education and Technologies: Sociability and Learning. Later, through the data acquired from the focal group, questions were extracted for the questionnaire, which was applied to 67 youthful; and with six participant professors, interviews were held. The literature review presented fundamental and theoretical regarding to the Higher Education in Brazil and in Brazilian Federal District, the profiles of the youth from pedagogy and his teaching, ICTs in education, learning mediated by ICTs and the pedagogic teaching practice and ICTs, taking as reference some authors as: Veloso (2008), Demo (2004), Bardin (2006) in methodology and also were used reference researches coordinated by UNESCO (2009, 2014, 2015). Through the achieved results, it was verified that pedagogy students and their professors perceives about the use of ICTs in pedagogic practices is very similar, since both verify this use and accept that it is used in a restrained way. The students admit that professors could be more daring, they could use diversified resources as videos and blogs, and professors also think the same way, but for reasons shown in this research, they are not always able to do so.